Development of Media Strike Zone for Pitching Learning Process on Softball - Irsyada, Roas (Universitas Negeri Semarang, 2019)
Softball games are one form of small ball games learned at school. In the softball game there is strike zone, which is an imaginary field between the elbow and the knee of a batter, and is above the home base. Students find it difficult to find the strike zone so that when throwing pitchers always â€œballâ€. when the game takes place students have difficulty determining between â€œstrikeâ€ and â€œballâ€. The need for learning media that can provide a real form of strike zone for students. This research is a development research that uses the stages of development of Borg and Gall. Based on product testing, the target media strike zone is very suitable with the softball game and can effectively provide information about the real shape of the strike zone in the softball game, as well as helping students to set targets and throw accuracy.